ANALISIS IDEOLOGI PADA NOVEL “AYAT-AYAT CINTA 2”: ANALISIS WACANA KRITIS MODEL VAN DIJK - Wahyu Ningsih; T Silvana Sinar; T Thyrhaya Zein (Balai Bahasa Sumatera Utara, 2019)
Ideology in a novel is a central concept in Critical Discourse Analysis. One of the novel authors who has a view of the surrounding existence through an ideology is Habiburahman El Shirazy. This studied aimed to find out how the ideology that underlies Ayat-ayat cinta's novel 2 by Habiburahman El Shirazy and what context triggers the ideology. To answer the research question, this research used van Dijk's Critical Discourse Analysis theory. This type of research was included in the type of content analysis research. The data in this study was sentences and paragraphs. Based on the results of the study, it was known that the ideology underlying the novel Ayat-ayat cinta's novel 2 by Habiburahman El Shirazy was an Islamic ideology and the context that triggers the ideology was how Habiburrahman El Shirazy views the western perception of Islam, views on dating in Islam, and based on the biography of Habiburrahman El Shirazy. Overall the Ayat-Ayat Cinta 2’s novel was a novel that reminds the reader of being able to at least change the mindset by reading and understanding the Qur'an well.